On generalized complex space forms satisfying certain curvature conditions - Praveena, M.M.; Bagewadi, C.S. (Carpathian Mathematical Publications, 2016)
We study Ricci soliton $(g,V,λ)$ of generalized complex space forms when the Riemannian, Bochner and $W_{2}$ curvature tensors satisfy certain curvature conditions like semi-symmetric, Einstein semi-symmetric, Ricci pseudo symmetric and Ricci generalized pseudo symmetric. In this study it is shown that shrinking, steady and expansion of the generalized complex space forms depends on the solenoidal property of vector $V$. Also we prove that generalized complex space form with conservative Bochner curvature tensor is constant scalar curvature.